2015
DOI: 10.1590/1807-1929/agriambi.v19n4p388-393
|View full text |Cite
|
Sign up to set email alerts
|

Lodo de esgoto e adubação mineral na recuperação de atributos químicos de solo degradado

Abstract: Objetivou-se, neste trabalho, estudar a influência do lodo de esgoto e adubação mineral na recuperação de atributos químicos de um Latossolo Vermelho degradado, cultivado há quatro anos, com eucalipto e braquiária. O delineamento experimental utilizado foi inteiramente casualizado com seis tratamentos e quatro repetições. Os tratamentos foram: T: testemunha (solo cultivado com eucalipto e braquiária sem uso do lodo de esgoto e adubação mineral); AM: solo cultivado com eucalipto e braquiária com adubação minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
0
18

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 12 publications
(25 reference statements)
7
21
0
18
Order By: Relevance
“…Carvalho et al (2015), when analyzing the organic fraction of five different sludge, found that more than 70% of carbon and 80% of nitrogen are in the organic compartment of sewage sludge. For this reason, sludge has been widely used as an amendment to improve soil chemical and physical characteristics and its application to soil has been indicated as one of the actions to mitigate climate change aiming at increasing the organic matter stock and hence soil carbon (BONINI et al, 2015;OUIMET et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Carvalho et al (2015), when analyzing the organic fraction of five different sludge, found that more than 70% of carbon and 80% of nitrogen are in the organic compartment of sewage sludge. For this reason, sludge has been widely used as an amendment to improve soil chemical and physical characteristics and its application to soil has been indicated as one of the actions to mitigate climate change aiming at increasing the organic matter stock and hence soil carbon (BONINI et al, 2015;OUIMET et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…These results are supported by the chemical characterisation of sewage sludge that altered the initial chemical characteristics of the soil. Moreover, as a result of the elevation of soil pH, there is an increase in the capacity to provide nutrients to the plants ( BOECHAT et al, 2015), and assistance in structuring the soil (BONINI et al, 2015) (Table 2). *-Significant effect at the 1% level of probability by F-test; **-Significant effect at the 5% level of probability by F-test; ns -not significant effect by F-test.…”
Section: Resultsmentioning
confidence: 99%
“…The use of sewage sludge in agriculture is still very questionable, due to the damage it can cause to human health and the natural environment, besides financial losses if it is incorrectly used (BONINI et al, 2015). A feasible technical alternative to the reuse of organic wastes is their use as organic fertilizer, provided that no heavy metals, pathogens and toxic components are present.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations